2013
DOI: 10.1002/app.39239
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosion epoxy coating enriched with hybrid nanozinc dust and halloysite nanotubes

Abstract: In this study, the performance of an epoxy coating with hybrid nanozinc dust and halloysite nanotube (HNT) fillers on the corrosion protection of a carbon steel substrate was investigated. The epoxy resin was mixed with a constant amount of nanozinc dust (1%) and different contents of HNTs (0, 0.5, 1, and 1.5%) with a high speed mixer. Fourier transform infrared spectroscopy and thermogravimetric analysis were used to analyze the interactions between the components in the coating material and the thermal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…Polymeric coatings provide a dense barrier for water and corrosive species from penetrating to the metal surface [16,17,18]. Epoxy resins are used for coating metals due to its strong chemical resistance and adhesion to metal surfaces [19]. However, when the epoxy-based barrier is damaged or scratched, the aggressive agents diffuse into the metal surface and cause corrosion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric coatings provide a dense barrier for water and corrosive species from penetrating to the metal surface [16,17,18]. Epoxy resins are used for coating metals due to its strong chemical resistance and adhesion to metal surfaces [19]. However, when the epoxy-based barrier is damaged or scratched, the aggressive agents diffuse into the metal surface and cause corrosion [5].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, at 0.1 and 0.5 wt.% TiO 2 ( Figure 6a) had a lower increase of corroded area at 480 h; 115 % and 44 %, respectively. This could be attributed to increased barrier properties against oxygen and water (Chen et al, 2006;Deyab & Keera, 2014) and due to filling the coatings' pores and voids (Moazeni et al, 2013). The observed increase at 1.0 wt.…”
Section: Tribological Evaluationmentioning
confidence: 89%
“…Moreover, the inherent corrosion protection capability of halloysite nanotubes and silica nanoparticles [82] will be an added advantage for epoxy coating incorporated with these inorganic materials loaded with corrosion inhibitors. Previously, it was shown that HNTs enhanced the corrosion protection capability of epoxy coating for a carbon steel substrate along with nanozinc dust [83]. Above all, the dimension of the epoxy monomer (diglycidyl ether of bisphenol A) (as per the molecular dynamic simulation studies) [84] is suitable to be loaded even inside the pores in meso-scale.…”
Section: Inorganic Nanomaterials As Self-healing Agent Containersmentioning
confidence: 99%